Mecanismos que afetam os estados estáveis alternativos e o efeito das mudanças climáticas sobre a invasão de uma planta submersa exótica. - Mormul, Roger Paulo (2011)
The alternative stable states and climate changes are the main themes discussed throughout the three chapters in this dissertation. In the first chapter I used a long term dataset of the Long Term Ecological Research program (LTER), in the Paraná River floodplain, to describe by the first time in this LTER site an alteration in the alternative state in one floodplain lake. The analyses showed that reduction in fish density, followed by the first record of submerged plant patches, started the shift from turbid to clear water state. The second chapter tested the grazing effects of large cladocerous and snails on phytoplankton and periphyton, respectively, to assess how this interaction affects the growth of an exotic submerged plant. The main results suggest that clear water state does not provide a successful invasion by exotic submerged plant, due to the reduction of number of sprouts in the presence of snails, because this is the main reproductive strategy of this plant. The third chapter is an experiment to test whether the increase of water temperature and/or the brownification process, both results of climate changes, may affect the growth of an exotic submerged plant. Evidences found showed that temperature does not affect growth of this plant. However, both phytoplankton and periphyton are affected negatively by darker waters. In this instance, the submerged plant has advantage due to reduction of competition, which leads to a successful invasion in darker waters. In summary, these three chapters contribute to improve the knowledge about mechanisms involved with alternative states in floodplain lakes, emphasizing also, the importance of including exotic species in this kind of study, due to the possibility of finding unusual patterns. In addition, the third chapter alerts to the fact that climate changes may provide enhance invasion by exotic submerged plants in humic lakes.